2013
DOI: 10.1371/journal.pone.0061360
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Microscopic Assessment of Compatible and Incompatible Interactions between Chickpea Cultivars and Fusarium oxysporum f. sp. ciceris Races

Abstract: BackgroundFusarium wilt caused by Fusarium oxysporum f. sp. ciceris, a main threat to global chickpea production, is managed mainly by resistant cultivars whose efficiency is curtailed by Fusarium oxysporum f. sp. ciceris races.MethodologyWe characterized compatible and incompatible interactions by assessing the spatial-temporal pattern of infection and colonization of chickpea cvs. P-2245, JG-62 and WR-315 by Fusarium oxysporum f. sp. ciceris races 0 and 5 labeled with ZsGreen fluorescent protein using confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 46 publications
2
60
0
3
Order By: Relevance
“…The yellowing pathotype induces progressive foliar yellowing with vascular discoloration and late plant death, while the wilting pathotype causes fast and severe chlorosis, flaccidity, vascular discoloration and early plant death [44].…”
Section: Pathogenic and Genetic Variability In Fusarium Oxysporum F mentioning
confidence: 99%
See 2 more Smart Citations
“…The yellowing pathotype induces progressive foliar yellowing with vascular discoloration and late plant death, while the wilting pathotype causes fast and severe chlorosis, flaccidity, vascular discoloration and early plant death [44].…”
Section: Pathogenic and Genetic Variability In Fusarium Oxysporum F mentioning
confidence: 99%
“…Races 0, 1B/C, 5, and 6 are found mainly in the Mediterranean Basin and California (USA) [23,40,44,46,47]. Race 1A has been reported in India, United States and the Mediterranean regions [20], whereas races 2 and 3 have been reported in Ethiopia, India, and Turkey [44,48,49] and race 4 has been reported in Ethiopia, India and Iraq [24,44,49].…”
Section: Pathogenic and Genetic Variability In Fusarium Oxysporum F mentioning
confidence: 99%
See 1 more Smart Citation
“…Invasion takes place mainly through the cotyledons and zones of the epicotyl and hypocotyl at the junction of or close to cotyledons, and to a lesser extent in the zone of root elongation and maturation (Jim enez-Díaz et al, 1989a;Stevenson et al, 1997). Later studies in infested hydroponic cultures showed that races 0 and 5 of the pathogen colonize the surface of the tap and lateral roots in both susceptible and resistant cultivars, and preferentially penetrate the meristematic cells of the root apex (Jim enez- Díaz et al, 1989a;Jim enez-Fern andez et al, 2013). Then, the fungus grows in the intercellular spaces of the root cortex to reach the central root cylinder and enter into the xylem vessels.…”
Section: Pathogen Biology and Ecologymentioning
confidence: 99%
“…Further colonization by the pathogen takes place by means of hyphal growth and microconidia carried in the vessels by transpiration stream, as well as by lateral mycelia spread to adjacent vessels from infected ones. The systemic colonization along the plant axis (i.e., the determinative phase of pathogenesis) is then followed by development of symptoms (i.e., the expressive phase) once intense colonization of xylem vessels in root and lower stem has occurred by 10e20 days after inoculation (Jim enez-Díaz et al, 1989a;Jim enez-Fern andez et al, 2013).…”
Section: Pathogen Biology and Ecologymentioning
confidence: 99%